EXPECTANCY VIOLATION IN PRIVATE SPACE RENTAL EXPERIENCED BY AIRBNB LOCAL HOST [Expectancy Violation In Private Space Rental Experienced By Airbnb Local Host] - Anisa Setya Arifina; Aulia Suminar ayu (Universitas Lambung Mangkurat, 2018)
Technological advancement drives a variety of changes, including lifestyles and urban society’sperspective. Yogyakarta is one of the tourist destinations in Indonesia that is developing the concept of smartcity to provide convenience for its citizens in their activities, especially in smart tourism. Technology is a facilitythat can help create smart tourism in a big city like Yogyakarta. The emergence of digital platforms that aregrowing vast every year is able to change market, employment and attract the attention of wide audiencebecause it forms new values that can support the realization of smart tourism. Through the integration of touristattractions into the Airbnb platform, Yogyakarta citizens can do business by sharing economy in attracting localand foreign tourists. One of the most prominent activities of this sharing economy is the utilization of privatespaces (bedrooms in private residence) into a public space that can be rented by tourists from all over the worldthrough online. This qualitative research aims to describe the expectancy violation on private space rentalexperienced by Yogyakarta citizens who are local hosts on the Airbnb platform using expectancy violationtheory. The results showed that the host gave a positive value of communicator reward valence to tourists usingprivate zones (kitchen, bathroom, and room) without hesitation and in accordance with the rules posted in thehouse. Each respondent has different ratings for negative communicator reward valence. This depends on thecultural variability of the guest and the field of experience of the host.Keywords: smart city, sharing economy, smart tourism, expectancy violation theory